2004
DOI: 10.1089/acm.2004.10.947
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Microwave Radiations Affect the Hypersensitive Response of Tobacco to Tobacco Mosaic Virus

Abstract: Nonthermal microwave radiations are effective on the hypersensitive response of tobacco to tobacco mosaic virus and their low-frequency modulation seems to be more bioactive than the continuous-flux of waves, particularly in the indirect water-mediated treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In addition, Betti (2004) reported a non-thermal effect of microwaves against plants and viruses at a sublethal temperature, and Wu and Yao (2010) confirmed visible changes of bacteria and fungi after microwave heat treatment by ESEM. Hence, in this study non-thermal effects were investigated by studying the morphological changes and SFs with and without microwaves at the same temperature.…”
Section: Effective Temperaturementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Betti (2004) reported a non-thermal effect of microwaves against plants and viruses at a sublethal temperature, and Wu and Yao (2010) confirmed visible changes of bacteria and fungi after microwave heat treatment by ESEM. Hence, in this study non-thermal effects were investigated by studying the morphological changes and SFs with and without microwaves at the same temperature.…”
Section: Effective Temperaturementioning
confidence: 97%
“…Meanwhile, there has been research demonstrating additional effects, beyond the purely thermal mode of inactivation. For example, distortion of membrane structure and function (Phelan et al, 1994), altered enzyme activity (Dreyfuss and Chipley, 1980), disruption of weak bonds (Betti et al, 2004), increased release of various substances (Woo et al, 2000;Celandroni et al, 2004;Campanha et al, 2007), and increased ionic strength due to an increased current within cells (Watanabe et al, 2000) have all been reported. However, all of the aforementioned research was conducted in the liquid, solid, or aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Betti et al (2004) reported a nonthermal effect of microwaves against plants and viruses at a sublethal temperature, and Wu and Yao (2010) confirmed visible changes of bacteria and fungi after microwave heat treatment by environmental scanning EM. Hence, in this study nonthermal effects were investigated by studying morphological changes and SFs with and without microwaves at the same temperature.…”
Section: Effective Temperaturementioning
confidence: 83%
“…High temperatures can cause denaturation and cell membrane damage [34], as well as alter enzymatic activities by disrupting weak bonds in active protein forms [35]. Moreover, MW irradiation exerts nonthermal effects on cell viability by interfering with cell signaling pathways, generating current within cells [36], and producing reactive oxygen species such as % OH [37]. Our previous studies indicated that a significant difference between MW irradiation and sole thermal treatment (Support information, Fig.…”
Section: Bioaerosol Inactivation Performance By Mw Irradiationmentioning
confidence: 97%
“…Similar finding was observed by Wu et al [8] that the microwave-irradiated P. fluorescens cells apparently had damaged membrane envelope as observed in the SEM images. Previous researches showed that MW can alter enzymatic activities by disrupting weak bonds in active protein forms [38], and produce reactive oxygen species (such as % OH) [37], which was used to damage membrane envelope. The SEM images of E. coli cells before and after MW irradiation ( Fig.…”
Section: Bioaerosol Inactivation Performance By Mw Irradiationmentioning
confidence: 99%